The shadow of the Haitian uprising on Hegel's thought - Maurer, Caterina (B@belonline, 2022)
According to Susan Buck-Morss, the victorious revolution of the slaves in Saint-Domingue provided Hegel with significant materials for conceiving the lordship-bondage relation described in the Phenomenology of Spirit (1807). In this essay it will be argued that, although Hegel was certainly aware of these events through to the press, in his works there are no clear elements supporting this thesis. Contextually it will be shown how Buck-Morss’ interpretation helps us to evaluate Hegel’s relevance to some enduring issues such as recognition and otherness, Eurocentrism and racism.